Cold knife versus laser cone biopsy for adenocarcinoma in situ of the cervix—a comparison of management and outcome. Issue 1 (1st January 2008) - Dalrymple, C.; Valmadre, S.; Cook, A.; Atkinson, K.; Carter, J.; Houghton, C. R.S.; Russell, P.
Abstract : Eighty-two patients with adenocarcinoma in situ of the cervix managed at Royal Prince Alfred Hospital were reviewed and data were collected on those treated by cold knife cone biopsy ( n = 38) and laser cone biopsy ( n = 44). No differences were found in patient age, cytologic or referral history, or outcomes. Having laser excision did not compromise margin status or subsequent management. Invasive disease was found in 24 patients, 16 of whom were managed conservatively with good outcome. Twelve of these were in the laser cone group. In those patients from both groups managed conservatively, there was only one recurrence, squamous preinvasive disease after 8 years. Laser cone biopsy is as effective as cold knife cone biopsy with no compromise of outcome for these patients.